Identifikasi Diskalkulia pada Anak Berkebutuhan Khusus Tunanetra dalam Mengenal Bilangan - Hanina Dewi Nastiti; Dwi Noviani Sulisawati; Lutfiyah (Jurnal Pendidikan Matematika (JPM), 2023)
Children with Special Needs are children who in education require specific services, different from children in general. Children with special needs are divided into 10 groups, namely: Blind, mentally retarded, dyslexic, hyperactive, mentally impaired, deaf, mute, autistic, disabled, gifted child. Blind is someone who has less accurate/poor vision compared to sighted people, even though they already assisted with visual aids, and cause them to require a lot of energy and time to do visual tasks. Therefore, blind children experience more difficulties in their education. Learning difficulties in mathematics are called dyscalculia. The most basic dyscalculia experienced by blind children is knowing numbers. So to find out the dyscalculia experienced by children with special needs who are blind in knowing numbers, the researchers took this research with a descriptive type of research and with a qualitative approach. The subjects of this study consisted of 2 students from class 4 of the blind group at SDLB Negeri Branjangan for the 2022/2023 academic year. The results of identification of dyscalculia in children with special needs in recognizing numbers are presented in the form of a description of each individual obtained from observation data, tests and interviews. The results of this study were that S1 subjects had dyscalculia on the characteristics of dyscalculia, namely visual motor associations and attention disorders, on the classification of dyscalculia, namely knowledge of numbers, on the types of dyscalculia, namely weak in planning and inability to do simple calculations. Whereas subject S2 has dyscalculia in the types of dyscalculia, namely weak in planning and inability to do simple calculations. Keywords: Children with Special Needs, Blind, Dyscalculia